Goal-directed dehydration therapy in sepsis and acute respiratory distress syndrome guided by volumetric hemodynamic monitoring - N. O. Khromacheva; E. V. Fot; V. V. Kuzkov; M. Yu. Kirov (Вестник анестезиологии и реаниматологии, 2020)
The aim of our study was to improve results of treatment of critically ill patients with sepsis and acute respiratory distress syndrome (ARDS) using the goal-directed dehydration therapy (DT).Sixty adult patients with sepsis and ARDS receiving mechanical ventilation for at least 24 hours were enrolled into a prospective randomized study. The patients were randomized into groups of dehydration guided either by extravascular (group of extravascular lung water index ‒ EVLWI, n = 30) or intravascular (group of global end-diastolic volume index ‒ GEDVI, n = 30) compartment. Dehydration was performed over 48 hours by administering diuretics or controlled extracorporeal ultrafiltration. We measured ventilation parameters, blood gases, and parameters of volumetric monitoring. The baseline characteristics of the patients did not differ between the groups. By 48 hours, the target fluid balance was achieved in both groups. In the EVLWI group at 48 hours, we found reduction of EVLWI by 15.4% (p < 0.001) and increase in PaO2/FiO2 by 23.3% as compared with baseline (p < 0.001). In parallel, we observed decrease in creatinine and urea (p < 0.05). In the GEDVI group, PaO2/FiO2 rose by 12.5% (p = 0.021), whereas EVLWI remained unchanged (p = 0.4). Maximal decrease in EVLWI and improvement of PaO2/FiO2 were achieved in direct ARDS.Thus, in patients with sepsis and ARDS the de-escalation goal-directed therapy resulted in the improvement of arterial oxygenation and organ function. The efficacy of dehydration was increased in direct ARDS. The extravascular compartment dehydration algorithm attenuated pulmonary edema and acute kidney injury more efficiently. Therefore, sepsis-induced ARDS may require personalized therapeutic approach.